CATALYZING EDUCATIONAL TRANSFORMATION IN THE DIGITAL AGE: ANALYZING THE TECHNOLOGICAL IMPLICATIONS ON MILLENNIALLEARNING IN INDONESIA - Hemi Pamuraharjo; Kardi; Nawang Kalbuana; Alwazir Abdusshomad (International Journal of Teaching and Learning, 2023)
In an era characterized by rapid technological advancement, this study delves into the transformative impact of technology on millennial learning in Indonesia. Through a mixed-methods approach encompassing surveys, assessments, interviews, and content analysis, the research examines the prevalence of technology usage among millennial students, its influence on learning outcomes, and its challenges. Key findings indicate that technology is an integral part of the educational journey for millennial learners in Indonesia, with widespread usage of smartphones, laptops, and tablets. Positive perceptions of technology's impact on learning outcomes and collaboration are evident. However, concerns about information quality and social media distractions reveal a nuanced relationship. The study's contribution lies in its in-depth exploration of this relationship, and its practical implications emphasize the need for responsible technology integration and digital literacy in education. As Indonesia's diverse educational landscape embraces the digital age, this research provides valuable insights for educators, policymakers, and researchers working to optimize millennial learning experiences.